Thieves of Bombay: United Artists, Colonial Copyright, and Film Piracy in the 1920s. (January 2014) - Govil, Nitin; Hoyt, Eric
This article examines Hollywood's attempts to curtail print duplication piracy in Bombay during the 1920s. The Thief of Bagdad, starring Douglas Fairbanks, was a massive international success for the Hollywood studio United Artists and their newly established Asian distribution network. Perhaps the most famous Hollywood release in India, Thief catapulted its star, Douglas Fairbanks, into the pantheon of Indian screen legends. In the late 1920s, United Artists discovered that Thief was being illegally distributed and exhibited in India and filed a series of legal actions in the Bombay courts. This article examines the extensive legal record of these cases—alongside letters, memos, and other studio correspondence—in order to reveal the topography of international distribution and its legal and non-legal circuits. We argue that Hollywood's problems in curtailing the so-called "Bombay piracies" demonstrate the contradictions of international intellectual property enforcement at a critical early juncture in media globalization.